Contract Grading in an Indigenous-Specific Section of Academic Reading and Writing - Gaudet, Loren (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
This essay outlines the experience of introducing a labour-based grading contract in a section of the University of Victoria’s standard introduction to academic reading and writing that was only open to students who self-identified as Indigenous. Labour-based grading contracts offer an alternative approach to conventional grading, in which a student’s grade is determined by the amount of labour that the student does over the semester. By emphasizing labour and learning, this approach to grading works towards decentering normalized whiteness in academic writing pedagogy. In this essay, I describe our labour-based contract, I explain how our class negotiated the contract, and I share some reflections on what went well and what I would do differently next time.